Odontogenic Factors Associated with Food Impaction in Patients Attending Periodontics OPD of Universal College of Medical Sciences - Adhikari, K; Dutta, K; Bali, H (Journal of Nepalese Prosthodontic Society, 2020)
Introduction: Food impaction is a common problem experienced by almost everyone during their lifetime. It is believed that the interproximal wedging of food normally occurs due to loss of integrity of the proximal contact and its location along with the contour of the marginal ridges and lack of papilla fill. The objective of the study was to assess the role of odontogenic factors for food impaction and identify the odontogenic factors most prevalent in patients attending Periodontics OPD of Universal College of Medical Sciences.Materials and Methods: A total of hundred subjects with natural dentition from the second molar to the second molar in both the maxillary and mandibular arches were enrolled in this cross-sectional study. Clinical parameters like pocket depth, bleeding index, and plaque index were recorded. The integrity of contact was recorded using dental floss. A study cast was fabricated for each subject. The presence of plunger cusps along with marginal ridge relationship, the position of the tooth in the arch, and contiguity of contact points were analyzed on it.Results: A significant association between plaque index score and food impaction was found (p=0.03). Of all the factors, loose contact showed a slightly significant positive correlation with a plaque index score (r= 0.19, p=0.05).Conclusions: Amongst all the odontogenic factors, loose contact is positively correlated with plaque index and food impaction is significantly associated with plaque score. The odds of food impaction were significant with the brushing technique employed and frequency of tooth brushing in the subjects.